2015
DOI: 10.1186/s12967-015-0424-1
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of proteins of metabolism by reverse phase protein microarrays identifies potential biomarkers of rare neuromuscular diseases

Abstract: BackgroundMuscle diseases have been associated with changes in the expression of proteins involved in energy metabolism. To this aim we have developed a number of monoclonal antibodies against proteins of energy metabolism.MethodsHerein, we have used Reverse Phase Protein Microarrays (RPMA), a high throughput technique, to investigate quantitative changes in protein expression with the aim of identifying potential biomarkers in rare neuromuscular diseases. A cohort of 73 muscle biopsies that included samples f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
(61 reference statements)
0
18
0
Order By: Relevance
“…The primary monoclonal antibodies developed in our lab and used in this study were: HSP60 (1:5,000), anti-NADH-9 (1:1,000), anti-β-F1-ATPase (1:20,000), anti-LDH-A (1:1,000) and anti-GAPDH (1:20,000) [ 53 , 54 ]. The monoclonal antibody specifically recognizing the human [ 15 ] and mouse (Molecular Probes) IF1 proteins were used at 1:200 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The primary monoclonal antibodies developed in our lab and used in this study were: HSP60 (1:5,000), anti-NADH-9 (1:1,000), anti-β-F1-ATPase (1:20,000), anti-LDH-A (1:1,000) and anti-GAPDH (1:20,000) [ 53 , 54 ]. The monoclonal antibody specifically recognizing the human [ 15 ] and mouse (Molecular Probes) IF1 proteins were used at 1:200 dilution.…”
Section: Methodsmentioning
confidence: 99%
“…The major limitation of quantitative RPPA is the availability of specific monoclonal antibodies (mAbs) against the proteins being studied. Figure 1 shows that the mAbs used in this study only recognized a single protein band at the expected molecular weight in human muscle extracts validating their utilization in RPPA techniques [ 11 13 ].
Fig.
…”
Section: Resultsmentioning
confidence: 69%
“…In contrast to the findings in muscle of sIBM, the biopsies of DM patients showed an enhanced expression of the mitochondrial protein Hsp60 and IF1 and a very large increase in the glycolytic PKM2. The βF1-ATPase/LDHA ratio, which has been recently described as a potential biomarker of neuromuscular diseases [ 13 ], failed in the discrimination of IMs except for sIBM patients, which showed an increase of the ratio. However, the βF1-ATPase/PKM2 ratio offered a reliable indicator to discriminate DM from any other IM or from control biopsies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mounting evidence has suggested that the pathological muscle wasting observed in dystrophies (e.g., DMD) might be due to reduced ATP availability required for maintenance of Ca 2+ homeostasis and fiber regeneration (Timpani et al, 2015 ). Bioenergetic pathway enzymes have recently shown to be relevant biomarkers of muscular and neuromuscular disease progression (Santacatterina et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%